PRINSIP AKUNTABILITAS PENGELOLAAN ANGGARAN UNTUK OPTIMALISASI KINERJA KEBIJAKAN PENDIDIKAN - Madekhan, Madekhan (Jurnal Review Politik, 2015)
Accountability variable in educational budget management is mainly for achieving performance indicators effectively. This paper confirm that the absence of accountability in the process of educational budget policy is dominant factor leading Indonesia toward human resource quality problems. Basically, involving accountability principle in every steps of educational budget management is indicated by a). A balanced relations among stakeholders b) transparency of public information, and c) people participation. In line of optimizing the performance of educational budget, the implementation of accountability formula will eradicate potency of corruption. Here, the bad side of the discretion and monopoly (D + M) in the policy process of educational budget by local and national authority will be reduced by functions of accountability (A) mechanism.